2010
DOI: 10.1080/00102202.2010.497404
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Investigation of Detonation Initiation in Profiled Tubes

Abstract: Detonation initiation in a tube with parabolic contraction and conical expansion was investigated numerically and experimentally. The optimized geometry of conical expansion with sine-shaped wall is proposed. The generalized diagram in the form of detonation curves at the contraction slope angle versus incident shock Mach number plane is presented. For solving the governing Euler equations, the numerical method based on finite volume approach with Godunov flux approximation adapted for multiprocessor systems i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The simulation results demonstrated a considerable effect of U-bend tube on detonation initiation. Semenov et al [46] proposed the parabolic contraction and conical expansion for detonation initiation in a tube. The shine shaped wall is proposed for optimized geometry of conical expansion.…”
Section: Reviews On Experimental Analysismentioning
confidence: 99%
“…The simulation results demonstrated a considerable effect of U-bend tube on detonation initiation. Semenov et al [46] proposed the parabolic contraction and conical expansion for detonation initiation in a tube. The shine shaped wall is proposed for optimized geometry of conical expansion.…”
Section: Reviews On Experimental Analysismentioning
confidence: 99%
“…16 The shock wave in these investigations was generated via a bursting diaphragm. Semenov et al 17 showed that sinusoidal conic expansion can lead to detonation initiation close to wall for failure of SDT inside the nozzle. When a suitably reactive gaseous mixture (e.g.…”
Section: Introductionmentioning
confidence: 99%